2018
DOI: 10.1186/s12887-018-1295-4
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization and reversal of child obesity in Andalusia using objective anthropometric measures by socioeconomic status

Abstract: BackgroundChildhood obesity continues to be a significant public health issue worldwide. Recent national studies in Spain show a stable picture. However, prevalence and trends differ by socio-economic status, age, and region. We present the trend in childhood excess weight prevalence, aged 8–15 years, in Andalusia from 2011-2012 to 2015–2016 by socio-economic status.MethodsUsing the cross-sectional Andalusian Health Surveys, objective anthropometric measures were taken for a representative sample of 8–15 year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…There is also evidence from other recent studies conducted in Australia and other developed countries of a plateau or, even, a decline in prevalence of overweight and obesity in children and adolescents [1, 19–23, 37]. It has been postulated that these trends reflect a positive effect of public health campaigns designed to prevent excess weight gain in children at the local, state and national level [38, 39].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…There is also evidence from other recent studies conducted in Australia and other developed countries of a plateau or, even, a decline in prevalence of overweight and obesity in children and adolescents [1, 19–23, 37]. It has been postulated that these trends reflect a positive effect of public health campaigns designed to prevent excess weight gain in children at the local, state and national level [38, 39].…”
Section: Discussionmentioning
confidence: 96%
“…The effect of SES is generally understood to be mediated through differences in weight-related behaviours [17, 37, 42, 43]. Compared to those from high SES background, ACT Year 6 children of low SES background reported lower levels of physical activity, higher levels of screen time and greater fast food and SSD consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, according to the NCD Risk Factor Collaboration (NCD-RisC), the obesity prevalence from 5-19 years all around the world has increased from 1992 to 2011 (9,8% vs 21,4%) and this upward trend continued until 2016 (NCD-RisC 2017). Despite some international and national works support this increase (Ruíz Pérez et al 2008;Salcedo et al 2010;Ng et al 2014), other authors noted a stabilization (Ogden et al 2016;Ramiro-González et al 2017;Hardy et al 2017;De Ruiter et al 2017;Aranceta-Bartrina and Pérez-Rodrigo 2018) and even in some cases a decrease (Schmidt Morgen et al 2013;Skinner and Skelton 2014;Koebnick et al 2015;Lazzeri et al 2015; Agencia Española de Consumo, Seguridad Alimentaria y Nutrición 2016; Miqueleiz et al 2016;Bygdell et al 2017;Sánchez-Cruz et al 2018;Herter-Aeberli et al 2019). In Australia (Hardy et al 2017), USA (Skinner and Skelton 2014;Ogden et al 2016) and some European countries (Schmidt Morgen et al 2013;Lazzeri et al 2015;Herter-Aeberli et al 2019) such a stabilization and downward trend have been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Las tasas más altas de sobrepeso y obesidad infantil se encontraron en los países de la cuenca del mediterráneo; España, Malta, Italia y Grecia (Aranceta-Bartrina, Gianzo-Citores, & Pérez-Rodrigo, 2020;Ortiz-Pinto et al, 2020). Esta prevalencia varía según el estatus donde se sitúen las familias, cuánto mayor estatus económico, menores tasas de sobrepeso y obesidad (Sánchez-Cruz, de Ruiter, Jiménez-Moleón, García, & Sánchez, 2018).…”
Section: Introductionunclassified